2020
DOI: 10.1186/s13023-020-01537-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of using the TBX6-associated congenital scoliosis risk score (TACScore) in genetic diagnosis of congenital scoliosis

Abstract: Background We previously reported a novel clinically distinguishable subtype of congenital scoliosis (CS), namely, TBX6-associated congenital scoliosis (TACS). We further developed the TBX6-associated CS risk score (TACScore), a multivariate phenotype-based model to predict TACS according to the patient’s clinical manifestations. In this study, we aimed to evaluate whether using the TACScore as a screening method prior to performing whole-exome sequencing (WES) is more cost-effective than using WES as the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 30 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…However, the sensitivity, specificity, and accuracy of the TACScore were 50, 85.8, and 83.5%, respectively, in our cohort, far lower than the values in DISCO studies. We inferred that results could be due to our smaller cohort size and that findings may more closely match those in previous reports if our cohort is expanded ( 16 , 25 ).…”
Section: Discussionsupporting
confidence: 83%
“…However, the sensitivity, specificity, and accuracy of the TACScore were 50, 85.8, and 83.5%, respectively, in our cohort, far lower than the values in DISCO studies. We inferred that results could be due to our smaller cohort size and that findings may more closely match those in previous reports if our cohort is expanded ( 16 , 25 ).…”
Section: Discussionsupporting
confidence: 83%
“…In the second stage, based on the title and abstract of the articles, 20 149 studies were excluded, and in the third stage, after careful study of the text of the remaining studies, 336 studies were eliminated. Finally, 36 studies which had examined the economic evaluation of NGS methods in the diagnosis of genetic diseases were included in this review 2,14–45 . Figure 1 shows the process of searching for studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies did not provide a justification for using the study perspective. In 16 studies, the discount rate was not reported 14,19,22,25,26,33–36,38,39,41–44 . In two study, the funding source was not mentioned 20,43,46 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations